2013
DOI: 10.1021/ie303440w
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hydroxypropyl-β-Cyclodextrin on the Solubility of an Antiarrhythmic Agent

Abstract: The aim of this work was to obtain an inclusion complex between HP-β-CD and amiodarone in order to increase the solubility of this active agent. Drug−cyclodextrin interactions in solution were investigated using phase solubility studies. The Fourier transform infrared spectroscopy (FT-IR) spectra revealed the presence of the interactions between the components of the inclusion complex. Changes in crystallinity of the drug inside the inclusion complex were confirmed by X-ray diffractometry (XRD) and differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 20 publications
5
11
0
Order By: Relevance
“…The DSC curve shows that AMH has a sharp melting endothermic peak at about 163.47 ºC, indicating a typical behavior of the anhydrous crystalline state. This DSC curve was similar to those in other studies (Paduraru et al, 2013, Riekes et al, 2010. During the DSC analysis the thermogram of HP-β-CD showed a very broad endothermic peak between 60 ºC and 110 ºC.…”
Section: Thermal Analysissupporting
confidence: 88%
See 3 more Smart Citations
“…The DSC curve shows that AMH has a sharp melting endothermic peak at about 163.47 ºC, indicating a typical behavior of the anhydrous crystalline state. This DSC curve was similar to those in other studies (Paduraru et al, 2013, Riekes et al, 2010. During the DSC analysis the thermogram of HP-β-CD showed a very broad endothermic peak between 60 ºC and 110 ºC.…”
Section: Thermal Analysissupporting
confidence: 88%
“…Similar results were observed with Methyl-β-CD and HP-β-CD by spray-drying and freeze-drying methods. This solid state form transition was also observed by Bankar and Mahatma (2012), Paduraru et al (2013) and Riekes et al (2010), when the amorphization of the compounds after complexation with cyclodextrins was demonstrated.…”
Section: X-ray Powder Diffraction Analysissupporting
confidence: 80%
See 2 more Smart Citations
“…Few studies were shown in the literature about the improvement of aqueous solubility and absorption of AMH including Elhasi, Astaneh, Lavasanifar(2007); Jouyban, Eghrary, Zarghami (2013);Martín-Algarra et al(1995); Paduraru et al (2013) and Riekes et al (2010).…”
Section: Introductionmentioning
confidence: 99%